Initial Reports of the Deep Sea Drilling Project 1984
DOI: 10.2973/dsdp.proc.73.138.1984
|View full text |Cite
|
Sign up to set email alerts
|

South Atlantic Cenozoic Paleoceanography

Abstract: Several suites of undisturbed cores obtained by continuous hydraulic piston coring provided material for the investigation of Cenozoic paleoceanography. The faunal record is complete, except for the early Eocene. The isotope records have gaps in the early Eocene and in the early and middle Miocene. Hundreds of samples were studied and thousands of analyses were carried out. Detailed results and conclusions are presented in several separate chapters of this volume. This report is a synthesis.Studies of calcite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…Since then, most reconstructions of the CCD have shown a clear shoaling trend from the Oligocene into the Miocene (e.g., van Andel, 1975;Heath et al, 1977;Hsu et al, 1984;Rea and Leinen, 1985), a trend similar to the one seen here. The study by Rea and Leinen (1985) of nearequatorial South Pacific sites is of particular interest, however, because of their observations of carbonate accumulation above the CCD.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Since then, most reconstructions of the CCD have shown a clear shoaling trend from the Oligocene into the Miocene (e.g., van Andel, 1975;Heath et al, 1977;Hsu et al, 1984;Rea and Leinen, 1985), a trend similar to the one seen here. The study by Rea and Leinen (1985) of nearequatorial South Pacific sites is of particular interest, however, because of their observations of carbonate accumulation above the CCD.…”
Section: Discussionsupporting
confidence: 74%
“…The principal paleoceanographic objective of Leg 115 was to use this new technology to recover a depth transect of continuously cored sedimentary sequences from the tropical Indian Ocean that would allow reconstruction of the dynamic features of the regional carbonate system through the late Cenozoic. Deep-sea drilling has long since established that dissolution levels in the different ocean basins have fluctuated markedly during the Cenozoic (e.g., Berger and Winterer, 1974;van Andel, 1975;Heath et al, 1977;Hsu et al, 1984;Rea and Leinen, 1985). In general, these studies have shown that long-term changes in the patterns of carbonate distribution have been similar between the major ocean basins, suggesting a global forcing mechanism perhaps linked to changing sea level or to a changing supply of carbonate to the oceans (Kennett, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Second, around the Congo estuary, the Congo Canyon immediately off Congo's west coast serves as a conduit for turbidity currents to carry away sediments from the Congo River to the oceans [53]. In addition, the branch of the northward flowing Benguela Current along the west coast of Africa can reduce sediment depositions on the northern side of the Congo River estuary [54], which may cause the potential MAR signal to emerge north of Congo's estuary in Figure 10b. Again, the GRACE data quality is another deciding factor: it is likely that GRACE data uncertainties in some of the estuaries in Figure 10 are so overwhelming that they suppress potential MAR signals.…”
Section: Discussion: Can We Detect Mars By Grace In the World's Majormentioning
confidence: 99%
“…Dating of the build-up of large ice-sheets on the Antarctic continent, with their strong feedback effects on the climatic development of the total globe, is still controversial (Hsu et al, 1984;Kennett, 1980;Webb et al, 1984;Robin, 1988).…”
Section: Introductionmentioning
confidence: 99%